Thermoregulatory behavior and orientation preference in bearded dragons - Black, I.; Tattersall, Glenn (Elsevier, 2017)
© 2017 Elsevier Ltd The regulation of body temperature is a critical function for animals. Although reliant on ambient temperature as a heat source, reptiles, and especially lizards, make use of multiple voluntary and involuntary behaviors to thermoregulate, including postural changes in body orientation, either toward or away from solar sources of heat. This thermal orientation may also result from a thermoregulatory drive to maintain precise control over cranial temperatures or a rostrally-driven sensory bias. The purpose of this work was to examine thermal orientation behavior in adult and neonatal bearded dragons (Pogona vitticeps), to ascertain its prevalence across different life stages within a laboratory situation and its interaction with behavioral thermoregulation. Both adult and neonatal bearded dragons were placed in a thermal gradient and allowed to voluntarily select temperatures for up to 8 h to observe the presence and development of a thermoregulatory orientation preference. Both adult and neonatal dragons displayed a non-random orientation, preferring to face toward a heat source while achieving mean thermal preferences of ~ 33–34 °C. Specifically, adult dragons were more likely to face a heat source when at cooler ambient temperatures and less likely at warmer temperatures, suggesting that orientation behavior counter-balances local selected temperatures but contributes to their thermoregulatory response. Neonates were also more likely to select cooler temperatures when facing a heat source, but required more experience before this orientation behavior emerged. Combined, these results demonstrate the importance of orientation to behavioral thermoregulation in multiple life stages of bearded dragons.